2020
DOI: 10.1002/wcms.1477
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bond design principles

Abstract: Hydrogen bonding principles are at the core of supramolecular design. This overview features a discussion relating molecular structure to hydrogen bond strengths, highlighting the following electronic effects on hydrogen bonding: electronegativity, steric effects, electrostatic effects, π-conjugation, and network cooperativity. Historical developments, along with experimental and computational efforts, leading up to the birth of the hydrogen bond concept, the discovery of nonclassical hydrogen bonds (C H…O, O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 131 publications
(210 reference statements)
2
71
0
Order By: Relevance
“…Already in the 1950s Linus Pauling explored together with Robert B. Corey the importance of hydrogen bonding in proteins [ 46 , 47 , 48 ], work which contributed to his Nobel Price in Chemistry, awarded to him in 1954 for his research into the nature of the chemical bond and its application to the elucidation of the structure of complex substances [ 49 , 50 ]. Up to now HBs have been the object of numerous experimental and theoretical investigations [ 45 , 51 , 52 , 53 ], and because of the complex interplay between different components, their nature is still subject of an ongoing debate [ 41 , 42 , 54 ]. Using intermolecular HBs as the key feature of base pairs selectivity GC base pairs with different bonding patterns and atomic organization were suggested [ 55 , 56 ], as well as different UBP estimating the HBs via calculated interaction energies [ 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…Already in the 1950s Linus Pauling explored together with Robert B. Corey the importance of hydrogen bonding in proteins [ 46 , 47 , 48 ], work which contributed to his Nobel Price in Chemistry, awarded to him in 1954 for his research into the nature of the chemical bond and its application to the elucidation of the structure of complex substances [ 49 , 50 ]. Up to now HBs have been the object of numerous experimental and theoretical investigations [ 45 , 51 , 52 , 53 ], and because of the complex interplay between different components, their nature is still subject of an ongoing debate [ 41 , 42 , 54 ]. Using intermolecular HBs as the key feature of base pairs selectivity GC base pairs with different bonding patterns and atomic organization were suggested [ 55 , 56 ], as well as different UBP estimating the HBs via calculated interaction energies [ 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the orbital interaction and the dipole–dipole interaction model, [ 45 ] it can be confirmed that hydrogen bond OH⋯O═C is stronger than OH⋯N owing to higher electronegativities of O (3.5) than N (3.0). [ 46 ] As a result, benefiting from more stable hydrogen bonding, the interface action and interfacial polarization can be enhanced for the BT–cCNT/PDMS composites, thereby leading to a relatively higher dielectric constant than that of BT–aCNT/PDMS as well as comparable dielectric loss. On the whole, tailor‐made dielectric features can be realized by the interaction between fillers via hydrogen bond.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that hydrogen bonds, unlike van der Waals forces, are saturated and directional. 19 The unique nature of hydrogen bonds significantly impacts the formation, particle size and polydispersity index (PDI) of U : C NPs. In particular, the molar ratios of U-SS-DOX and Ara-C might exert an influence on the supramolecular assembly process.…”
Section: Co-assembly Of U-ss-dox and Ara-c And Optimum Dose Ratio Screeningmentioning
confidence: 99%